An experimental approach to estimating the value of grain moisture information to farmers in Bangladesh. (December 2018) - Akter, Tahmina; Islam, M. Serajul; Haque, Md. Mojammel; Lowenberg-DeBoer, J.
Abstract: In the developing world grain storage losses are high and in humid areas inadequate grain drying is often a source of storage problems. Farmers and traders depend on traditional grain moisture estimation methods which are subject to a wide error margin. Grain storage decisions could be improved if farmers and traders had a low cost grain moisture meter that fit their needs. The goal of this study was to determine the desired grain moisture meter functionality and to estimate the value of grain moisture measurement for small holder farmers and for small-scale grain traders, using Bangladesh as a case study. This study was based on interviews with 140 randomly selected Bangladeshi rice farmers in 2016 and 2017, discussions with millers at 30 rice mills and a voucher based moisture meter sales program. It shows that except for rice kept for seed and home consumption, most Bangladeshi farmers sell their rice shortly after harvest to satisfy cash needs and to eliminate storage risks. They say that they would store more rice on-farm if they had better storage methods including cost-effective grain moisture testing. Survey results show that the average farm storage loss was 52 kg or 563 Taka (US6.78) annually. Using experimental economics methods, farmers were given the opportunity to purchase a probe type grain moisture meter through vouchers with a range of prices. Twenty three of the 140 of the participants (i.e. 16%) purchased at an average of price of 374 Taka (i.e. US4.67). No farmer purchased a voucher price over 800 Taka (US10.00). Those who purchased moisture meters had larger farms and produced more rice than those who did not exercise the voucher. They were also younger on average, have more education and more off farm income than non-purchasers. Highlights: Average farm storage loss was 52 kg with a value of 563 Taka (US6.78) annually. The average purchase price of the moisture meter was 374 Taka (i.e. US4.67). No farmer purchased at a voucher price over 800 Taka (US10.00). Those who purchased moisture meters had larger farms and produced more rice. Purchasers were also younger, more educated and had more off farm income.